Identification of targets of CD8⁺ T cell responses to malaria liver stages by genome-wide epitope profiling. - Julius Clemence R Hafalla; Karolis Bauza; Johannes Friesen; Gloria Gonzalez-Aseguinolaza; Adrian V S Hill; Kai Matuschewski (PLoS Pathogens)
CD8⁺ T cells mediate immunity against Plasmodium liver stages. However, the paucity of parasite-specific epitopes of CD8⁺ T cells has limited our current understanding of the mechanisms influencing the generation, maintenance and efficiency of these responses. To identify antigenic epitopes in a stringent murine malaria immunisation model, we performed a systematic profiling of H(2b)-restricted peptides predicted from genome-wide analysis. We describe the identification of Plasmodium berghei (Pb) sporozoite-specific gene 20 (S20)- and thrombospondin-related adhesive protein (TRAP)-derived peptides, termed PbS20₃₁₈ and PbTRAP₁₃₀ respectively, as targets of CD8⁺ T cells from C57BL/6 mice vaccinated by whole parasite strategies known to protect against sporozoite challenge. While both PbS20₃₁₈ and PbTRAP₁₃₀ elicit effector and effector memory phenotypes in both the spleens and livers of immunised mice, only PbTRAP₁₃₀-specific CD8⁺ T cells exhibit in vivo cytotoxicity. Moreover, PbTRAP₁₃₀-specific, but not PbS20₃₁₈-specific, CD8⁺ T cells significantly contribute to inhibition of parasite development. Prime/boost vaccination with PbTRAP demonstrates CD8⁺ T cell-dependent efficacy against sporozoite challenge. We conclude that PbTRAP is an immunodominant antigen during liver-stage infection. Together, our results underscore the presence of CD8⁺ T cells with divergent potencies against distinct Plasmodium liver-stage epitopes. Our identification of antigen-specific CD8⁺ T cells will allow interrogation of the development of immune responses against malaria liver stages.